4CPS-203 Pharmacoeconomic analysis of the management of gaucher disease in a paediatrics hospital. (March 2019) - Attjioui, H; Adade, C; Aliat, Z; Cheikh, A; Mefetah, H; Bouatia, M
Abstract : Background: Gaucher disease is a rare, autosomal recessive genetic disorder caused by a deficiency in the enzymatic activity of glucocerebrosidase. Although enzymatic replacement therapies are present, their high costs are a brake on therapeutic management. The current literature on the assessment of the economic and clinical value of treatment remains insufficient to date. Purpose: Determine the overall average cost of managing Gaucher disease per patient and establish a cost-impact analysis comparing the different treatments. Material and methods: We conducted a prospective, descriptive and analytical study at the paediatrics hospital. The variables for the calculation of the direct costs were collected using a checklist and the cost-benefit analysis was carried out using a questionnaire for the treating doctor, and also on the assessment of haematological and organomegaly parameters, before and during the treatment. Results: The study involved three patients treated for type 1 Gaucher disease, with an average age of 11±3.60 years and an average weight of 28±19.2 kg. The patients used three different treatments and the cost of each treatment is represented in table 1 below: The average annual direct cost per patient of the management of Gaucher disease in our study was estimated at €186, 363.30±€95, 156.05/year. Conclusion: The lowest cost was of the alpha-taliglucerase treatment. The average direct cost has as a predominant expenditure the treatment of the cause (€149, 622.38) which corresponds to 80% of the total cost. Clinically, good efficacy on haematological parameters and organomegaly was observed for the three patients as well as an improvement in the quality of life of the patients whose diagnosis was made early. References and/or acknowledgements: Thank you to the team hospital. No conflict of interest.